A fuzzy logic control in adjustable autonomy of a multi-agent system for an automated elderly movement monitoring application - Mostafa S.A.; Mustapha A.; Mohammed M.A.; Ahmad M.S.; Mahmoud M.A. (Elsevier Ireland Ltd, 2023)
Accident prevention; Assisted living; Computer circuits; Fuzzy logic; Multi agent systems; Adjustable autonomy; Ambient assisted living; Autonomous decision; Complex environments; Elderly remote care; Fall detection; Fuzzy logic control; Movement monitoring; Autonomous agents; aged; Article; automation; decision making; falling; fuzzy logic; human; movement (physiology); patient autonomy; patient monitoring; priority journal; algorithm; automated pattern recognition; computer simulation; movement (physiology); physiologic monitoring; procedures; theoretical model; Aged; Algorithms; Computer Simulation; Fuzzy Logic; Humans; Models, Theoretical; Monitoring, Physiologic; Movement; Pattern Recognition, Automated